ENTERPRISE DATA MIGRATION SUCCESS PATTERNS: LESSONS FROM LARGE-SCALE TRANSFORMATIONS - Suresh Kumar Somayajula (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Background: Organizations increasingly face the challenge of migrating enterprise data systems from traditional databases to cloud platforms, yet comprehensive frameworks for ensuring success in such transitions remain limited. While existing literature addresses technical aspects of data migration, there is a notable gap in empirical evidence supporting specific architectural and strategic approaches. Methods: This study analyzed 150 enterprise-scale data migration projects across healthcare, finance, and manufacturing sectors between 2020-2024. We employed a mixed-methods approach, combining quantitative performance metrics with qualitative assessments of architectural decisions and risk mitigation strategies. Projects were evaluated using a standardized framework measuring migration completion time, data integrity, system downtime, and post-migration performance improvements. Results: Analysis revealed that organizations implementing a three-phase migration strategy achieved 40% faster completion times compared to traditional approaches. Healthcare sector migrations utilizing enhanced encryption protocols and staged data transfer methods demonstrated zero security incidents across 45 implementations. Organizations adopting automated validation frameworks reduced post-migration data reconciliation efforts by 65%. Cloud platform transitions showed an average 30% improvement in query performance and 50% reduction in operational costs. Conclusions: This research contributes to the field of enterprise data migration in three significant ways: (1) establishing empirical validation of architectural patterns through quantitative analysis of 150 enterprise implementations, (2) developing a novel risk assessment framework specifically calibrated for highly regulated sectors, and (3) providing a reproducible methodology for evaluating migration success factors across diverse industry contexts. These contributions address a critical gap in the literature regarding evidence-based approaches to large-scale data transitions.